2021
DOI: 10.1111/1742-6723.13877
|View full text |Cite
|
Sign up to set email alerts
|

Validity and reliability of the Interagency Integrated Triage Tool in a regional emergency department in Papua New Guinea

Abstract: Objective: The Interagency Integrated Triage Tool (IITT) is a novel, three-tier triage system recommended by the World Health Organization. The present study sought to assess the validity and reliability of a pilot version of the tool in a resource-limited ED in regional Papua New Guinea. Methods: This pragmatic prospective observational study, conducted at Mount Hagen Provincial Hospital, commenced 1 month after IITT implementation. The facility did not have a pre-existing triage system. All ED patients prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…3 , 4 Limited data suggest the IITT can identify ED patients with urgent care needs, including those with COVID-19. 5 , 6 , 7 …”
Section: Introductionmentioning
confidence: 99%
“…3 , 4 Limited data suggest the IITT can identify ED patients with urgent care needs, including those with COVID-19. 5 , 6 , 7 …”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have determined the tool's sensitivity to be 70.8% and 77.8% for identifying patients with time‐sensitive diagnoses such as acute coronary syndrome and ruptured ectopic pregnancy. 3 , 4 Collectively, these figures are within the performance range of other triage systems to detect critical illness. 5 For instance, a recent systematic review reported the sensitivity of established triage tools to identify severe sepsis as between 36% and 74%.…”
Section: Discussionmentioning
confidence: 64%
“…The IITT has shown similar performance for urgent non‐COVID conditions. Previous studies have determined the tool's sensitivity to be 70.8% and 77.8% for identifying patients with time‐sensitive diagnoses such as acute coronary syndrome and ruptured ectopic pregnancy 3,4 . Collectively, these figures are within the performance range of other triage systems to detect critical illness 5 .…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…[10,11,19,21,22] Pilot evaluations assessing its validity and reliability have demonstrated acceptable performance. [23,24] Evidence and experience Although triage tools vary in their composition, validation studies suggest that many share similar weaknesses, including suboptimal sensitivity for the detection of time-critical illness. [5,6] In fact, a 2011 systematic review concluded that, in general, triage systems are supported by "limited and often insufficient evidence."…”
Section: Triage and Emergency Care In Low-and Middle-income Countriesmentioning
confidence: 99%